Genetic loci associated with renal function measures and chronic kidney disease in children: the pediatric investigation for genetic factors linked with renal progression consortium - Wuttke, Matthias; Wong, Craig S.; Wühl, Elke; Epting, Daniel; Luo, Li; Hoppmann, Anselm; Doyon, Anke; Li, Yong; Sözeri, Betül; Thurn, Daniela; Helmstädter, Martin; Huber, Tobias B.; et al. (Nephrology, dialysis, transplantation, 2016)
AbstractBackground. Chronic kidney disease (CKD) in children is characterized by rapid progression and a high incidence of end-stage renal disease and therefore